PENGARUH PENGETAHUAN INVESTASI, MOTIVASI DAN INFLUENCER SAHAM TERHADAP MINAT INVESTASI GENERASI MILENIAL DI PASAR MODAL - Addiin Arrahmi; Nursanita (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2023)
The development of business and information technology has had a major impact on the economy of various sectors, especially the technology-based business sector. Increasingly sophisticated technology is utilized by the Indonesia Stock Exchange (IDX) to increase the number of investors in the capital market. The millennial generation is a potential target of the IDX program to attract the interest of the millennial generation to invest in the capital market. The millennial generation is considered to have sufficient knowledge and strong motivation. In addition, the millennial generation is considered to tend to follow public figures to do things. The use of stock influencers is considered capable of influencing and attracting the interest of the millennial generation to invest. The purpose of this study was to determine the effect of investment knowledge, motivation and stock influencers on the millennial generation's investment interest in the capital market. The population of this study were postgraduate students and alumni of undergraduate students at the Faculty of Economics STIE Indonesia Jakarta with a sample of 172 respondents. The sampling technique uses purposive sampling, collecting data using a questionnaire. The results of this study indicate that investment knowledge, motivation and stock influencers simultaneously have a significant positive effect on the millennial generation's investment interest in the capital market.